PENGARUH KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN SERTA DAMPAKNYA PADA KEPERCAYAAN PELANGGAN PT. MITRA INTERTRANS FORWARDING CABANG PALU - Ratnasari, Siti (Katalogis, 2015)
This research aims to know and analyze the effect of: (1) service quality on satisfaction at PT. Mitra Intertrans Forwarding Palu Branch, (2) customer value on satisfaction at PT. Mitra Intertrans Forwarding Palu Branch,(3) satisfaction on customer trust at PT. Mitra Intertrans Forwarding, Palu Branch. This Research involves 150 respndent that have been determined using methode. Based on the result of Structural Equation Modeling (SEM) it shows that: (1) service quality performs positive and significant effect on satisfaction at PT. Mitra Intertrans Forwarding Palu Branch, (2) customer value performs positive and significant effect on satisfaction at PT. Mitra Intertrans Forwarding Palu Branch,(3) satisfaction performs positive and significant effect customer trust on PT. Mitra Intertrans Forwarding Palu Branch.